Penafsiran Ismail Ascholy terhadap ayat-ayat hijab: analisis terhadap akun media sosial instragam - Nahilah, Hilyatun; Mubarok, Mochammad Syahroni (Maliki Interdisciplinary Journal, 2024)
Tafsir in the process has experienced development, from the initial stages in oral form, then in writing, until it developed in the digital realm through various platforms, such as Facebook, Instagram, YouTube, Twitter and so on. Through social media, users can express themselves, have discourse, including spreading the knowledge they have. One of the social media account users who actively uses the Instagram platform in his preaching is Ismail Ascholy. In particular, in this article there are two main focuses, namely the biography of Ismail Ascholy and his interpretation of the hijab verses on his Instagram social account. The author uses a qualitative method and completes it using a phenomenological approach to knowledge. The data sources used are divided into two types, namely primary and secondary data sources. The primary data source is the interpretation of the QS. An-Nur verse 31 is explained in writing in Ismail Ascholy’s post. Meanwhile, secondary sources come from other literature that is relevant to the discussion on this topic, in the form of articles, journals, books, and the like. The method used in this article is to collect documentation type data. Starting by analyzing every post on Ismail Ascholy’s account about the hijab. After the data was collected, the author processed the data using a descriptive model so that from there we would know how Ismail Ascholy understood the instructions regarding the rules for wearing the hijab.